2010
DOI: 10.1111/j.1745-7599.2010.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Family presence during cardiopulmonary resuscitation: Using evidence-based knowledge to guide the advanced practice nurse in developing formal policy and practice guidelines

Abstract: With this evidence-based knowledge the APN will be able to disseminate information to facilitate collaborative change in current practices surrounding staff education, decision making, and self-governance. The APN can then address controversial changes when developing formal policies and procedures, which will increase patient satisfaction and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
(43 reference statements)
0
23
0
12
Order By: Relevance
“…Survey results and guidelines provided by the American Association of Critical-Care Nurses were considered in updating existing policy on FPDR within the health care system. A primary barrier to FPDR, identified in our study, and in other research, [4][5][6] was fear of interference by a family member during resuscitation and a need for someone to attend to the family. Although chaplains already responded to codes and were able to tend to and be responsible for a patient's family members during resuscitation events, chaplains were not always available, especially at night.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Survey results and guidelines provided by the American Association of Critical-Care Nurses were considered in updating existing policy on FPDR within the health care system. A primary barrier to FPDR, identified in our study, and in other research, [4][5][6] was fear of interference by a family member during resuscitation and a need for someone to attend to the family. Although chaplains already responded to codes and were able to tend to and be responsible for a patient's family members during resuscitation events, chaplains were not always available, especially at night.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, FPDR helps a patient's family members understand that everything possible was done for their loved one. The review 4 indicated that families thought that FPDR was their right and that they were more at ease when able to view resuscitation efforts firsthand. Family members reported that FPDR provided closure and helped in the grieving process.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 The family facilitator role holds much promise for reducing (a) the risk of families getting in the way, (b) patients' anxiety about families' responses, and (c) families' misunderstanding of events. 28,46 The AACN Practice Alert 28 also recommends the formation of institutional policies and procedures in support of family presence (Table 3). Patients' preferences for family presence might be different and concerns might be fewer if this study were replicated at a site where family facilitators and policies are in place.…”
Section: Discussionmentioning
confidence: 99%